Gene action governing pearl millet stover nitrogen and in Vitro digestibility and opportunities for improvement - Choudhary, S.; Bidinger, F.R.; Hash, C.T.; Vadez, Vincent; Blümmel, Michael (2012)
Two pearl millet [Pennisetum glaucum (L.) R. Br.] stover fodder traits, nitrogen content (N) and in vitro digestibility, were targeted to investigate their modes of inheritance and to assess the scope for improving them relative to a base population. From a full-sib (FS) base population of pearl millet variety ‘ICMV 221’ three high and low nitrogen and three high and low in vitro digestibility FS were selected. Crosses were made for high × high (H × H), low × low (L × L) and high × low (H × L) FS trait contrasts and evaluated at Patancheru in the rainy seasons of 2007 and 2008. The high and low nitrogen FS parents contrasted 0.85 and 0.72% for nitrogen (N). In the crosses stover N contents were: HN × HN = 0.85%, LN × LN = 0.73% and HN × LN = 0.80% (P < 0.05). The high and low digestibility FS parents contrasted 43.3 and 40.3% for in vitro digestibility. In the crosses stover in vitro digestibilities (D) were: HD × HD = 43.7%, LD × LD = 40.3% and HD × LD = 42.2% (P < 0.05). The intermediate results of H × L crosses strongly indicates the additive nature of the stover quality traits nitrogen and in vitro digestibility and suggest the application of cyclic breeding methods for increasing stover nitrogen content and in vitro digestibility in pearl millet.